Trading offshore: evidence on banks' tax avoidance - Dominika Langenmayr; Franz Reiter (The Scandinavian Journal of Economics, 2022)
Little is known about how banks shift profits to low-tax countries. Because of their specific business model, banks use other profit-shifting channels than non-financial firms. We propose a novel and bank-specific method of profit shifting: the strategic relocation of proprietary trading to low-tax jurisdictions. Using regulatory data from the German central bank, we show that a 1 percentage point lower corporate tax rate increases banks' fixed-income trading assets by 3–4 percent and trading derivatives by 9 percent. Suggestively, this increase does not arise from a relocation of real activities (i.e., traders); instead, it stems from the relocation of book profits.
Keywords: 330; Multinational banks; profit shifting; tax avoidance